Antimicrobial Susceptibility Trends among Pathogens Isolated from Blood: A 6-Year Retrospective Study from a Tertiary Care Hospital in East Sikkim, India - Yangzom, Tsering; Tsering, Dechen Chomu; Kar, Sumit; Kapil, Jyotsna (Journal of Laboratory Physicians, 2020)
Background Bloodstream infections (BSIs) are one of the frequent nosocomial infections among hospitalized patients. To understand the local epidemiology and evolving antimicrobial drug resistance of blood-borne pathogens, we analyzed the distribution and antibiotic sensitivity profile of organisms causing BSI in our hospital-based study.Materials and Methods We reviewed retrospective data of laboratory-confirmed BSIs, from January 2013 to December 2018. Causative organisms and their antibiotic susceptibility profile of primary and secondary BSI reports were determined from BacT/Alert and Vitek systems findings (bioMérieux). A 6-year multidrug resistance indexing was done to document the resistance pattern of the commonly isolated organisms.Results A total of 1,340 (10.2%) BSIs were reported from 13,091 blood cultures. Organisms were frequently isolated from the younger population (≤20 years), especially from ages < 1 year (20.8% of total BSIs). Majority of pathogens were bacterial (97.1%) whereas 2.9% were fungal in origin. Monomicrobial growth was recorded in over 98% of BSIs. Gram-positive and gram-negative bacteria isolated were 518 (39.8%) and 783 (60.2%), respectively. Commonly isolated organisms were coagulase-negative Staphylococci (29.4%), Escherichia coli (19.8%), Klebsiella species (13.5%), Salmonella species (9.4%), and Staphylococcus aureus (7.5%). Multidrug-resistance index was observed highest in Acinetobacter species followed by Pseudomonas aeruginosa and S. aureus.Conclusion Overall, there has been a gradual decline in the reporting of BSI. However, infections by gram-negative bacilli and multidrug-resistant organisms remain persistently high. Ages < 20 years were the vulnerable group, with infants < 1 year contributing to the maximum number of BSI cases caused by both bacteria and fungi. Therefore, additional methods are required to study the origin and causation of these infections, particularly among vulnerable patients.
Keywords: antimicrobial drug resistance; drug resistance; bloodstream infection; nosocomial infections